CH4/N2 Adsorptive Separation on Zeolite X/AC Composites - Cai Long Xue; Wen Ping Cheng; Wen Ming Hao; Jing Hong Ma; Rui Feng Li (Journal of Chemistry)
A series of zeolite X/activated carbon (AC) composites were prepared from the same starting materials at various activation time. The corresponding modified samples were obtained by being treated with diluted NH4Cl solution. The relationship between porosity development, surface properties, and CH4/N2 adsorption performance was investigated. The increase of micropore volume is beneficial to the improvement of CH4 and N2 adsorption capacity, but more sensitive for CH4. In addition, the polar functional groups of zeolite X/AC composites may enhance CH4 adsorption capacity. More importantly, both developing micropore structure and surface modification contributed to enhance the adsorption selectivity αCH4/N2. As the optimum sample of these studies, HZAC(24) showed CH4 adsorption capacity of 17.3 cm3/g and the highest adsorption selectivity αCH4/N2 of 3.4. The CH4 and N2 adsorption isotherms of all samples can be well fitted by the Langmuir–Freundlich model. HZAC(24) showed an excellent cyclability of adsorption/desorption of CH4 with a neglectable capacity loss after subsequent cycles. Moreover, HZAC(24) displayed relatively rapid adsorption kinetics. These properties of zeolite X/AC composites are essential for the adsorptive separation of CH4 from N2 in the pressure swing adsorption (PSA) process.